2017
DOI: 10.3892/ijo.2017.4167
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid metabolites and derivatives inhibit CDK activity: Novel insights into aspirin's chemopreventive effects against colorectal cancer

Abstract: Aspirin's potential as a drug continues to be evaluated for the prevention of colorectal cancer (CRC). Although multiple targets for aspirin and its metabolite, salicylic acid, have been identified, no unifying mechanism has been proposed to clearly explain its chemopreventive effects. Our goal here was to investigate the ability of salicylic acid metabolites, known to be generated through cytochrome P450 (CYP450) enzymes, and its derivatives as cyclin dependent kinase (CDK) inhibitors to gain new insights int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 50 publications
3
47
0
2
Order By: Relevance
“…Furthermore, several reports have demonstrated that a residue Cyc38 of p65-NF-κB is essential for the specific binding/interaction to the DNA in different tumor cells [40,43,46,66]. Interestingly, recent studies suggested that polyphenols may mediate their anti-proliferative effects in colon cancer cells through targeting the cyclin-dependent kinase (CDK) activity [67,68]. As the NF-kB family is tightly involved in cell cycle regulation through actions on the CDK/cyclin-dependent kinase inhibitors (CKI) system [69], here, Calebin A, through inhibition of NF-kB DNA binding, may directly suppress cell cycle activation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several reports have demonstrated that a residue Cyc38 of p65-NF-κB is essential for the specific binding/interaction to the DNA in different tumor cells [40,43,46,66]. Interestingly, recent studies suggested that polyphenols may mediate their anti-proliferative effects in colon cancer cells through targeting the cyclin-dependent kinase (CDK) activity [67,68]. As the NF-kB family is tightly involved in cell cycle regulation through actions on the CDK/cyclin-dependent kinase inhibitors (CKI) system [69], here, Calebin A, through inhibition of NF-kB DNA binding, may directly suppress cell cycle activation.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, GA proposed to have chemopreventive effects in colorectal cancer (Dachineni et al, ). It is known that cyclin dependent kinases (CDKs) including CDK1, CDK2, CDK3, CDK4, CDK5, and CDK6 are key regulators of the cell cycle regulation, which activated through binding with cyclins, including cyclin A, B, C, and D. When CDK activated via binding to cyclins, facilitated the progression of cell cycle, for example, from G 2 to M phase.…”
Section: Pharmacological Properties Of Gentisic Acidmentioning
confidence: 99%
“…So the inhibitors of CDK may prove to be useful in cancer prevention and treatment (Malumbres & Barbacid, ). In a study (Dachineni et al, ), the ability of SA metabolites in CDK inhibition was investigated. It was shown that GA interferes with Asp146 in CDK1 through –COOH group and Arg 135 in Cyclin B1 through –OH group and consciously inhibited it.…”
Section: Pharmacological Properties Of Gentisic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, aspirin may also indirectly activate AMPK through other processes [14]. It has been reported that aspirin and its metabolites regulate cyclin-dependent kinase (CDK) [15,16] and Wnt/β-catenin signaling [17,18].…”
Section: Ivyspringmentioning
confidence: 99%